Culturual Shock Faced By Main Characters On Spanglish Movie - Salsa Bela Angelina Panjaitan; I Nengah Sudipa; I Nyoman Arya Wibawa (PT. ALHAFI BERKAH INDONESIA, 2023)
This research focuses on Cultural shock faced by the main character in James L. Brook's movie Spanglish. The aims of this undergraduate thesis are to identify what stages of cultural shock faced by main characters in the movie and analyze how is the character performing their problem-solving process. In collecting the data the student used note-taking and documentation method and techniques. The data was obtained by watching the movie and taking notes on each scene. Following the data analysis stating Oberg's theory about the stages of Culture Shock and for Problem-solving process used Qin's theory. This research uses qualitative method, and presenting the data formally and informally. The result from the analysis is that Cristina and Flor experienced all of the stages of Cultural shock, which are honeymoon, crisis, adjustment, and adaptation stages. In the crisis stage, many problems and difficulties have been found. The process of problem-solving pursues a term problem and its analysis result. Furthermore, it pursues the problematic and circumstances that accompany the particular problem and appear during its solving.